2017
DOI: 10.1038/s41598-017-00269-7
|View full text |Cite
|
Sign up to set email alerts
|

Role for the ATPase inhibitory factor 1 in the environmental carcinogen-induced Warburg phenotype

Abstract: Most tumors undergo metabolic reprogramming towards glycolysis, the so-called Warburg effect, to support growth and survival. Overexpression of IF1, the physiological inhibitor of the F0F1ATPase, has been related to this phenomenon and appears to be a relevant marker in cancer. Environmental contributions to cancer development are now widely accepted but little is known about the underlying intracellular mechanisms. Among the environmental pollutants humans are commonly exposed to, benzo[a]pyrene (B[a]P), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Several mechanisms are known to be involved in the toxicity of B[a]P and ethanol towards the liver—oxidative stress, cell death, inflammation and mitochondrial dysfunction [ 33 , 36 , 40 , 71 , 72 , 73 , 74 ]. In addition, another process that has been highlighted in this context is membrane remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms are known to be involved in the toxicity of B[a]P and ethanol towards the liver—oxidative stress, cell death, inflammation and mitochondrial dysfunction [ 33 , 36 , 40 , 71 , 72 , 73 , 74 ]. In addition, another process that has been highlighted in this context is membrane remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, B[a]P has also been reported to impair epinephrine-induced lipolysis in adipocytes through interference with β-adrenoceptors, and this effect was associated with weight gain in mice [19]. B(a)P has also been found to induce cellular metabolic reprogramming, associated to the increase of ATP Inhibitory Factor 1 expression which might rely on β 2 AR activation [24,25].…”
Section: Potential Metabolic Effects From Interference With β 2 Ar-fumentioning
confidence: 69%
“…We found that B[a]P induced an increase in IF1 content of mitochondria; its silencing not only prevented lactate production, that is, glycolysis, but also increased cell death [82]. Taken all these results into consideration, we can therefore suppose that the change in pH m we detected might also be involved in the activation of IF1 by B[a]P. Besides a role of pH m alterations, the NHE1 activation induced by B[a]P also appeared to be involved in the related metabolic reprogramming.…”
Section: -2-2-h + Dynamics and Energy Metabolismmentioning
confidence: 79%
“…We previously identified that B[a]P could potentiate the expression of IF1, the physiological inhibitor of the F0F1ATPase [82]. As shown by Campanella and coworkers [111], an increase in IF1 in HeLa cells was responsible for an inhibition of autophagy.…”
Section: A N U S C R I P Tmentioning
confidence: 87%